Final assessment of nursing students in clinical practice: Perspectives of nursing teachers, students and mentors. Issue 23 (22nd June 2017) - Helminen, Kristiina; Johnson, Martin; Isoaho, Hannu; Turunen, Hannele; Tossavainen, Kerttu
Abstract : Aims and objectives: To describe the phenomenon of final assessment of the clinical practice of nursing students and to examine whether there were differences in assessments by the students and their teachers and mentors. Background: Final assessment of students in clinical practice during their education has great importance for ensuring that enough high‐quality nursing students are trained, as assessment tasks affect what the nursing student learns during the clinical practice. Design: This study used descriptive, cross‐sectional design. Methods: The population of this study comprised nursing students ( n  = 276) and their teachers ( n  = 108) in five universities of applied sciences in Finland as well as mentors ( n  = 225) who came from five partner hospitals. A questionnaire developed for this study contained questions about background variables as well as structured questions scored on a four‐point scale, which also allowed the respondents to provide additional comments. Results: When comparing the results related to nursing teachers' presence in the final assessment situation, it was found that teachers and mentors evaluated this as being carried out more often than nursing students suggested. Nursing students noted that fair and consistent assessment is carried out more often than nursing teachers thought. Mentors and teachers said that honest and direct criteria‐based final assessment was carried out more often than nursing students evaluated. Conclusions: Nursing students and mentors need support from educational institutions and from nursing teachers in order to ensure the completion of a relevant assessment process. Relevance to clinical practice: The findings of this study highlight an awareness of final assessment process. It is desirable to have a common understanding, for example, of how the assessment should be managed and what the assessment criteria are, as this will ensure a good quality process.